PENTINGNYA MOTIVASI, PEMASARAN DAN MEREK BAGI PELAKU INDUSTRI KECIL MENENGAH (STUDI KASUS PADA IKM IBU TATIK KOTA TANJUNGPINANG) - Risnawati Risnawati; Risgar Friassantano; Nanda Kristia Santoso; Adelya Adelya; Alfauza Alfauza; Hamallya Hamallya (LPPM ITB AAS Indonesia Surakarta, 2023)
One of the MSMEs registered in Tanjungpinang City, namely Ms. Tatik's MSMEs located in the Bukit Cermin Village, Ms. Tatik's MSMEs produces light snacks, namely Onion Cakes. From the results of our community service, Ibu Tatik's cake business only uses home production capacity with limited capital. The problem with Ibu Tatik's IKM is that there is no brand or logo provided by Ibu Tatik's IKM, so that many consumers do not know about the MSME business that is at Tugu Pahlawan street address. In this study we collected data and information by making observations or behavior using the senses based on events that were captured at the time the incident took place. In developing the brand for Ms. Tatik's MSMEs, it is necessary to combine the role of brand management within the organization as an internal factor and brand recognition as an external factor. In developing a brand there are 4 stages which include beginning and underprivileged brand, emerging brand, established brand, historic brand. It was concluded that the brand is important for Ms. Tatik's MSMEs because it is a representation of the goods produced. So that the mark needs to be registered to get protection for exclusive rights in the form of economic and moral rights as well as for legal certainty in the event that a third party uses the mark without permission. . Keywords: MSME, Management, Enterpreunerial Motivation. Marketing, Digital Marketing, Brands